2021
DOI: 10.1177/1045389x211018850
|View full text |Cite
|
Sign up to set email alerts
|

Thermorheological properties of magnetorheological grease and its thermomagnetic coupling mechanism

Abstract: A heating phenomenon exists in the service process of magneto-rheological devices. For magnetorheological devices using magnetorheological grease (MRG) as the working medium, changes in the medium’s rheological behaviors caused by temperature increase will generate challenges in the reliable service of the devices. With laboratory-prepared MRG as the research object, MRG rheological property laws under different temperatures and magnetic field intensities are investigated, and the magnetic properties of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Currently, materials with drastic changes in viscoelasticity are MR fluids [23], greases [2], [10], [24] and plastomers [25], [26]. The fluid nature of the materials allows CIP to move around freely enough within the matrix, allowing more defined formations of CIP chains.…”
Section: Overview Of Magnetorheologymentioning
confidence: 99%
“…Currently, materials with drastic changes in viscoelasticity are MR fluids [23], greases [2], [10], [24] and plastomers [25], [26]. The fluid nature of the materials allows CIP to move around freely enough within the matrix, allowing more defined formations of CIP chains.…”
Section: Overview Of Magnetorheologymentioning
confidence: 99%
“…Wang et al [8] observed that temperature has an effect on the apparent viscosity, and this effect decreases with the increase of magnetic field strength. Pan et al [9] found that MRG and grease have similar thermal rheological characteristics. The yield stress and consistency coefficient decrease with the increase of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during impact, the compressibility of MRG enables the objects to be protected from peak forces, and particles chains formed by magnetic fields can further dissipate the complex impact energies. Inspired by these advantages, certain achievements have been made at the macro-mechanical level, such as the relationship between stress-strain, shear yield stress-magnetic flux densities, and modulus variation, etc [29][30][31][32]. Although these macroscopic characteristics corroborate the influence of microstructural changes on materials properties, regular experiments cannot accurately reveal the instantaneous natures and complexity of such variations.…”
Section: Introductionmentioning
confidence: 99%